1999
DOI: 10.1046/j.1365-294x.1999.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of microsatellites for individual assignment: the North Atlantic redfish (genus Sebastes) species complex as a case study

Abstract: We used the four redfish taxa (genus Sebastes) from the North Atlantic to evaluate the potential of multilocus genotype information obtained from microsatellites in assigning individuals at two different levels of group divergence. We first tested the hypothesis that microsatellites can diagnostically discriminate individual redfish from different groups. Second, we compared two different methods to quantify the effect of number of loci and likelihood stringency levels on the power of microsatellites for redfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 39 publications
7
107
0
1
Order By: Relevance
“…Although the large assemblage of species in Sebastes was thought to have resulted from an ancient explosive speciation event (Johns and Avise 1998), many species complexes that exhibit few or almost no morphological differences were shown to have speciated more recently upon the application of molecular markers, including variations in mitochondrial DNA (mtDNA), allozymes, microsatellites or AFLPs (Roques et al 1999;RochaOlivares et al 1999b;Kai et al 2002a, b;Narum et al 2004;Hawkins et al 2005). Such species complexes may be evidence for active speciation mechanisms within the genus (Alesandrini and Bernardi 1999;Hyde and Vetter 2007), and may provide useful examples for the study of speciation in marine fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the large assemblage of species in Sebastes was thought to have resulted from an ancient explosive speciation event (Johns and Avise 1998), many species complexes that exhibit few or almost no morphological differences were shown to have speciated more recently upon the application of molecular markers, including variations in mitochondrial DNA (mtDNA), allozymes, microsatellites or AFLPs (Roques et al 1999;RochaOlivares et al 1999b;Kai et al 2002a, b;Narum et al 2004;Hawkins et al 2005). Such species complexes may be evidence for active speciation mechanisms within the genus (Alesandrini and Bernardi 1999;Hyde and Vetter 2007), and may provide useful examples for the study of speciation in marine fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier genetic studies of Sebastes species in the eastern North Atlantic have focused mainly on species identification, using a variety of molecular markers (for example, Altukhov and Nefyodov, 1968;Nefyodov, 1971;Johnson et al, 1973;Naevdal, 1978;Dushchenko, 1987;Naevdal, 1989, 1991a, b;Johansen et al, 1993;Nedreaas et al, 1994;Roques et al, 1999a;. These studies have shown that interspecific differentiation is generally low in redfish species, whereas both allozyme and microsatellite studies of S. mentella indicated limited population differentiation (Dushchenko, 1987;Nedreaas and Naevdal, 1991b;Nedreaas et al, 1994;Roques et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The first and second alternatives can be tested upon a reliable identification and description of both sibling species and the posterior establishment of their distributional range. A molecular phylogeny using nuclear genes and fastevolving markers, such as microsatellites, as have been used in other studies (Roques et al 1999, An et al 2009) could also give clues about the potential of interbreeding between these The nature of microsatellite DNA loci has made them particularly amenable for genetic analyses of natural marine populations, and the applications of these markers are increasing in evaluating genetic structure of rockfishes (Sekino et al 2001, Gómez-Uchida & Banks 2005, Sotka et al 2005, and species identification problems (Pampoulie & Daníelsdóttir 2008). No doubt, these analyses can be strongly recommended to address the genetic divergence and speciation of Southern rockfishes in more detail.…”
Section: Discussionmentioning
confidence: 99%